The Impact of Budget Allocation on Regional Development Performance in 2024 - Siti Wulan Sari; Ahmad As'adi; Alvi Nuramalia; Haerul Ihsan; Intan Nabila; Maesaro Sulandari; Gama Pratama (Ecobankers : Journal of Economy and Banking, 2026)
This study examines the impact of budget allocation on regional development performance with a case study in Cirebon Regency. The main problem is related to the effectiveness of the Regional Revenue and Expenditure Budget (APBD) in encouraging development in the era of fiscal decentralization, where budget allocation is often not optimal. The purpose of the research is to describe the pattern of budget allocation for the 2024 APBD, analyze development performance based on economic, social, and infrastructure indicators, and measure the influence of budget allocation on this performance. The method used is a literature study with a descriptive qualitative approach, analyzing APBD, PPAS, and related literature documents. The results of the study show that the Cirebon Regency Budget in 2024 is IDR 3.919 trillion, with revenue dominated by central transfers (76%) and operating expenditure reaching 73%, which limits productive investment. Development performance was hampered by high fiscal dependence and the dominance of routine spending, although capital allocation contributed positively to infrastructure. Factors such as participatory planning and increased PAD are needed to increase effectiveness. This study recommends the transformation of fiscal governance towards inclusive and sustainable development.